PENGARUH PEMBERIAN PUPUK KOTORAN WALET TERHADAP PERTUMBUHAN BIBIT KOPI LIBERIKA (Coffea liberica) DI MEDIA GAMBUT - Sopiana Sopiana; Sarwendah Ratnawati Hermanto; Elan Adiat Nur (Politeknik Negeri Ketapang, 2022)
Coffee (Coffea sp) is one of the plantation commodities that has a fairly high economic value and plays an important role as a source of foreign exchange for the country. The importance of coffee plants in the Indonesian economy makes coffee production increase. Swallow dung is an organic fertilizer which contains C-Organic 50.46%, N/total 11.24%, and C/N Ratio 4.49 with a pH of 7.97%, Phosphorus 1.59%, Potassium 2.17%, Calcium 0.30%, Magnesium 0.01%. This study aims to determine the effect of fertilizer application on the growth of Liberika coffee seedlings on peat media. The study used a completely randomized design (CRD) consisting of 5 treatments and 5 replications, so that there were 25 experimental units, each experimental unit consisting of 3 samples so that the total number of samples was 75 samples. The treatments were W0: 0 g/polybag, W1: 40 g/ polybag, W2: 60 g/polybag, W3: 80 g/polybag, W4: 100 g/polybag. The dry parameters observed were plant height, stem diameter, leaf length, leaf width, root length, and plant weight. The results showed that the application of swallow fertilizer had a significant effect on the parameters of plant height, stem diameter, leaf length, leaf width, root length, and dry weight of liberica coffee plants. The dose of 100 g/polybag of swallow manure was the best dose that affected the vegetative growth of the coffee liberika plant.